Brazil - Toward a More Inclusive and Effective Participatory Budget in Porto Alegre : Volume 2. Annexes - World Bank (World Bank, Washington, DC, 2012)
This report is about effective participatory budgeting in Porto Alegre. The process was initiated during the early years of re-democratization and decentralization in Brazil, following the end of the military dictatorship in 1985. The 1988 constitution initiated a process of decentralization and tax reforms that created the fiscal space for municipalities to make more significant public investment decisions. A plethora of participatory governance institutions have since proliferated in Brazil, most importantly, municipal policy councils and participatory budgeting bodies. The Participatory Budget (OP) was formally introduced in Porto Alegre under the leadership of the Workers' Party in coalition with pro-democracy social movements. Although initially fraught with difficulties due to fiscal constraints, the OP in Porto Alegre became gradually more systematic over time. Today, the OP has a complex methodology for organizing participation in a city of over 1.4 million inhabitants, as well as for prioritizing public investments based on three main criteria: unmet basic needs, population, and citizen preferences. However, the OP constitutes one element in a broader complex system of participatory governance in Porto Alegre. Findings on the poverty and fiscal impacts of OP in Brazil suggest that OP is a participatory mechanism that has significant potential for pro-poor distributive impacts that lead to poverty reduction outcomes in the long run. Its ability to have a positive impact on fiscal performance is less evident.